Anaerobic co-digestion of bioplastics as a sustainable mode of waste management with improved energy production – A review. (February 2021) - Abraham, Amith; Park, Hyojung; Choi, Okkyoung; Sang, Byoung-In
Highlights: Bioplastics are identified as a major waste stream in modern society. Anaerobic co-digestion can be an efficient mode of bioplastic waste management. Co-digestion of bioplastics improves biogas production during anaerobic digestion. The use of bioplastic bags in anaerobic digesters simplifies the biowaste collection process. Abstract: The world of bioplastics has expanded rapidly in recent decades, and the new waste stream generated is creating major barriers to waste processing. Anaerobic co-digestion is to be considered one of the best options for the efficient processing of bioplastic waste due to its minimal space requirements, lower degrees of environmental pollution, and renewable energy generation. The higher carbon to nitrogen (C/N) ratio of bioplastics poses a challenge to anaerobic digestion, but co-digestion with lower C/N ratio biowastes can efficiently degrade bioplastics and improve biogas production in the system. In the future, the collection of organic waste in biodegradable plastic bags makes the waste management process easier for anaerobic digestion plants. The present review paper discusses current trends of bioplastic usage, degradation strategies, and the potential of anaerobic co-digestion for waste management with improved energy production in anaerobic digesters.